2954-2023 - IEEE Recommended Practice for Overhead Transmission Line Design (IEEE, 2024)
Large collection of peer-reviewed IEEE and other industry standards and guidelines related to overhead transmission line design, testing, construction, and maintenance is summarized in this recommended practice. This includes aspects such as structures, foundations, conductors, insulators, hardware, and electrical effects. It identifies the documents in an organized and comprehensive fashion along with explanations of the material presented within each document and when a particular document should be considered.
Keywords: Electric lines.